Holistic and individualized interventions for behavioral and psychological symptoms of dementia - Naoya Tsukii (Annals of Alzheimer's and Dementia Care - Peertechz Publications, 2022)
Since "living well with dementia" is a concept that varies from person to person, the care provided is expected to be customized to the individual needs of each person with dementia. Support is expected to involve shared decision-making between people with dementia and their caregivers, and a comprehensive geriatric assessment within the framework of the International Classification of Functioning, Disability, and Health is expected to be conducted to help these persons with dementia realize their goals. Additionally, the Plan-Do-Check-Act cycle is expected to be regularly implemented to verify the effectiveness of the intervention. Although the disability of the individual with dementia increases as the disease progresses, it is important to support them to live positively by reducing their difficulties in daily living.